Impact evaluation of goat production technologies in farmers’ flocks - GOEL, A K; SHARMA, R B; SINGH, M K (The Indian Journal of Animal Sciences, 2013)
A study was conducted to determine the impact of goat production technologies under farmers’ flocks under the transfer of technology programme in 4 adopted villages having sizable goat population. Operational villages were provided with goat production technologies viz. improved breeding bucks (6), reproductive and regular health care (preventive and curative), managemental practices and products technologies. Regular visits were undertaken in operational villages at fortnight intervals for 3 years. Data related to natural mating by institute’s Barbari bucks and Non - descript village bucks, pregnancy diagnosis, progeny born, reproductive parameters and gynaco-obstetrical disorders were collected on prescribed schedules. Goat farmers were also motivated to adopt improved goat production practices by arranging on and off campus trainings besides health camps and kishan gosthies at their door steps. Kidding rate was numerically higher in all village flocks sired by improved Barbari bucks and was statistically higher in village-Barka Nagla. Irrespective of villages, kidding rate in goats sired by Barbari buck was significantly higher to Non-descript buck. A visible improvement (12%) in terms of multiple births (twins and triplets) following introduction of improved Barbari breeding bucks was observed. A 2- fold increase in triplet births was also recorded. Introduction of Barbari bucks in these villages also upgraded the non descript goat population which fetched higher price in the market. Anoestrus and abortion were encountered as major reproductive disorders with a relative incidence of 35.14 and 15.32%, respectively. During and after kidding, retention of placenta (ROP) and insufficient dilatation of cervix (ring womb) were encountered as major obstetrical problems with an incidence of 12.61 and 10.81%, respectively. Reduction in occurrence of reproductive disorders over the years also indicated a favorable impact of goat reproduction and production technologies. Study indicated a viable impact of breed improvement after introducing superior Barbari breeding bucks and other goat production technologies in the terms of increased multiple births and overall kidding rates with reduction in occurrence of pre and post parturient disorders in progeny born out of Barbari bucks and goat population. Long term adoption of such practices will help in prevention of dilution of prolific Barbari breed in future.